Biology and population dynamics of the black clam villorita cyprinoides (Gray, 1825) in the vembanad lake - Anju, A. V. (KUFOS, 2018)
Abstract- The black clam, Villorita cyprinoides is an economically important bivalve found along the Indian coast and exclusively sustains the molluscan fishery of Vembanad Lake. Present study analyses the biological aspects and population parameters of Villorita cyprinoides in the Vembanad Lake. It is a continuous breeder with two peak periods of spawning viz, June – August and December – February. Gonad and condition indices were found directly related to the reproductive cycle, clams with fully matured gonad have maximum value of GI and CI, while digestive gland index was peak during the post spawning period. The overall male to female ratio observed was 1:1.2. The allometric studies in Villorita cyprinoides have revealed the existence of significant correlation between various morphological characters. The population parameters of this species were assessed to evaluate the status of the stock. The asymptotic length (L∞) was 46.2mm, while growth coefficient (K) was 0.9 yr-1 and initial condition parameter (t0) was -0.016 yr. It attained a length of 27.72mm at the end of first year, 38.66mm at second year and 43.15mm at the end of third year. The estimated total mortality (Z), natural mortality (M), fishing mortality (F) to be 3.07 yr-1, 1.37 yr-1 and1.70 yr-1 respectively. The recruitment pattern was continuous over the year with two major peaks (August and January). The exploitation rate (E = 0.553) which surpassed the maximum exploitation rate (Emax = 0.539) suggests the need to regulate harvesting. The Socio-economic survey attempted in the present study reveal the major livelihood problems faced by the clam fishers of Vembanad Lake, are low income, intensive labour and indebtedness.